Africa : Is This the Turning Point? - Khan, Mohsin; Fischer, Stanley; Hernandez-Cata, Ernesto (Washington, D.C. : International Monetary Fund, 1998)
This paper examines the experience of Sub-Saharan Africa (SSA) to answer the question of whether the region is at a turning point in its economic fortunes. The improvement in growth reflects in part a rise in the utilization of existing capacity. To be sustained, however, a high rate of growth will require an increase in investment rates and/or an increase in total factor productivity-i.e., an improvement in the technological, political, administrative and economic factors that raise the rate of return on both capital and labor. The close link between investment and growth in developing countries over the long term is evident in the empirical growth literature. For developing countries in general, the elasticity of growth with respect to the investment/GDP ratio has been found to lie within the range of 0.3-0.5. Although increasing investment is crucial, action is also needed in many complementary areas in order to raise productivity and growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet